Evaluation of Risk Factors for Prediction of Outcome in Fetal Spectrum of Atrioventricular Septal Defects. (19th September 2013) - Bader, Rima S.; Punn, Rajesh; Silverman, Norman H.
Abstract Background Atrioventricular septal defects (AVSD) are very commonly diagnosed in utero. Heterotaxy/chromosomal abnormalities frequently coexist with AVSD. However, outcomes of fetal AVSD are not precisely known. We attempted to define mortality risk factors in AVSD. Method We retrospectively searched our database, electronic records, and echocardiograms with diagnosis of fetal AVSD from 2003 to 2012. We investigated the following risk factors: atrial situs, heart rate/rhythm, ventricular dominance/morphology, atrioventricular valve regurgitation, cardiothoracic ratio, ejection fraction, and extracardiac anomalies. Results Forty‐five fetuses with a median gestational age of 28 weeks (17.5–37.1) were determined to have AVSD during the 10 years, of which 12 were either lost to follow‐up (6) or underwent termination (6). There were 16 deaths (48%); two died in utero. Isomerism was identified in 17 of 45 (37%) fetuses (11 left atrial, 6 right atrial isomerism) and chromosomal abnormalities were identified in 12 (27%). Twenty‐eight of 33 fetuses, not lost to follow‐up or terminated, had extracardiac anomalies which had associated increased mortality (57% vs. 0%, P = .04). Heart block (75% vs. 43%, P = .12), left ventricular noncompaction (80% vs. 43%, P = .17), and isomerism (63% vs. 41%, P = .28) were associated with mortality but without statistical significance. Twenty‐five of 45 (56%) had unbalanced AVSD. Positional abnormalities of the great arteries or semilunar valve stenosis were present in 20/45 (44%) while venous anomalies were present in 16/45 (36%). Presence of ventricular dominance, atrioventricular valve regurgitation, elevated cardiothoracic ratio, or diminished ejection fraction were not associated with mortality. Conclusion Overall mortality rate for fetuses with AVSD was 48%. The presence of extracardiac anomalies is an independent risk factor for prediction of fetal or neonatal demise. Heart block, isomerism, and noncompaction in fetal AVSD appear to be associated with poor outcomes as well but did not reach statistical significance. This information is useful for counseling parents with fetus AVSD.